A comparison of the effects of three selected exercise intensities on the lactate recovery ability of elite distance runners. - Séguin, Robert A. (University of Ottawa (Canada), 1992)
Six elite, male, cross-country runners were assessed on a motorized treadmill for aerobic endurance capacity using blood lactate (HLa) recovery ability ($\Delta$La) in three square-wave endurance exercise tests (SWEET) with repeat intervals below (S1), at (S2), and above (S3) threshold (OBLA). Each SWEET was composed of 6 possible repeat intervals (OVERs) followed by active rest intervals (UNDERs) of the same distance where $\Delta$La = (HLa) $\sb{\rm OVER}$- (HLa) $\sb{\rm UNDER}$. S1 and S2 interval (HLa) values where stable whereas S3 interval (HLa) values drifted upwards over the 6 repeats. Interval HR values were rising slightly over the SWEET durations. Interval VO$\sb2$s were similar in value over the SWEET durations. $\Delta$La (mM) values were significantly increased (p 0.05) from 0.66 $\pm$ 0.06 for $\Delta$La$\sb{\rm S1}$, to 1.31 $\pm$ 0.45 for $\Delta$La$\sb{\rm S2}$, to a nearly significant increase (p = 0.06 for N = 6) to 1.58 $\pm$ 0.79 for $\Delta$La$\sb{\rm S3}$, $\Delta$La$\sb{\rm S1}$ and $\Delta$La$\sb{\rm S2}$ were 40% and 80% of $\Delta$La$\sb{\rm S3}$ values. Post hoc analysis revealed the source of statistical significance as all SWEET repeats except 1 and 6. Within SWEET repeat $\Delta$Las were not significantly different. Lactate recovery ability increases were attributed to either the increased utilization of La as a fuel during periods of increased metabolic rate or the augmented flow of La down concentration gradients from lactate producing space to lactate usage and storage space. Implications for runners were that excursions at or above threshold levels were compensated for by increased $\Delta$La, but that the number of repeat intervals possible during racing and or training may vary for individuals and should be considered.
Keywords: Biology, Animal Physiology.